Acute toxicity and the 28-day repeated dose study of a Siddha medicine Nuna Kadugu in rats - Ramaswamy Ramaswamy; Prathyusha Nettam; Saranya Ruthiramoorthi; Sumathy Haridass; Mohanavalli Kutuva; Priya Raju; Venkhatesh Jayakothanda; Babu Chidambaram; Manickavasakam Kumarasamy; Thanikachalam Sadagopan (BMC, 2012)
Abstract Background Nuna Kadugu (NK), a Siddha medicine prepared from leaves and fruits of Morinda Pubescens, used for the treatment of various skin diseases. Though NK has been widely used for several decades, no scientific report was available on its safety. Present study was undertaken to demonstrate the oral toxicity of NK in Sprague Dawley rats. Methods Acute and 28-day repeated oral toxicity studies were performed following OECD test guidelines 423 and 407, respectively, with minor modifications. In acute oral toxicity study, NK was administered at 2000mg/kg b.wt., p.o and animals were observed for toxic signs at 0, 0.5, 1, 4, 24 h and for next 14 days. Gross pathology was performed at the end of the study. In repeated dose, the 28- day oral toxicity study, NK was administered at 300, 600 and 900 mg/kg b.wt./p.o/day. Two satellite groups (control and high dose) were also maintained to determine the delayed onset toxicity of NK. Animals were observed for mortality, morbidity, body weight changes, feed and water intake. Haematology, clinical biochemistry, electrolytes, gross pathology, relative organ weight and histopathological examination were performed. Results In acute toxicity study, no treatment related death or toxic signs were observed with NK administration. In the repeated dose study, no significant differences in body weight changes, food / water intake, haematology, clinical biochemistry and electrolytes content were observed between control and NK groups. No gross pathological findings and difference in relative organ weights were observed between control and NK treated rats. Histopathological examination revealed no abnormalities with NK treatment. Conclusion Acute study reveals that the LD50 of NK is greater than 2000mg/kg, b.wt. in fasted female rats and can be classified as Category 5. 28-day repeated oral toxicity demonstrates that the No Observed Adverse Effect Level of NK is greater than 900 mg/kg b.wt./day, p.o in rats. There were no delayed effects in NK satellite group. In conclusion, NK was found to be non-toxic in the tested doses and experimental conditions.